Subsiden, Emisi Karbon Dan Fisik Tanah Gambut Terbakar Dan Tidak Terbakar Di Areal Konservasi Gambut - Nuriman, Muhammad (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2024)
Today, peatland fires cause peat soil changes and release carbon emissions. The area protected as a peat conservation area in 2019 was not spared from fire incidents, where the land is an area with a maintained groundwater level and has monitoring data on groundwater level and peat thickness. This paper aimed to identify the subsidence, carbon emissions, and several physical properties of peat soil in burned and unburned peat conservation areas. The variables measured were hydraulic conductivity, subsidence, bulk density, water content, carbon content, and carbon emissions. The number of observation plots was 6 plots, with three (3) unburned plots and three (3) burned plots located in the Peat Conservation Area in Ketapang Regency, West Kalimantan. The six observation plots were in peatlands with the Typic Haplohemists subgroup, and shrub land cover. The results showed that the hydraulic conductivity and carbon content in unburned and burned land were not statistically and significantly different (P>0.05). The values of bulk density, water content, subsidence, and carbon emissions on burned land were significantly different (P<0.05) compared to unburned land. Subsidence in unburned locations was 1.83 ± 0.44 cm, while in burned areas it was 5.56 ± 0.84 cm. The amount of subsidence affects the amount of carbon emissions resulting from the loss of peat layers, namely on unburned land it was 9.24 ±3.13 tonnes/ha, and 35.53±3.73 tonnes/ha on burned land. The results of carbon emissions from subsidence caused by land fires can be determined as a basic emission factor for these two land conditions with similar peat characteristics. Keywords : Peat Fires, Peat Conservation Areas, Physical Properties of Peat, Subsidence, Carbon Emissions